Analisis Efektivitas Mesin Produksi Menggunakan Pendekatan Failure and Mode Effect Analysis dan Logic Tree Analysis - Dhita Febriyanti; Erika Fatma (JIEMS (Journal of Industrial Engineering and Management Systems), 2018)
This research uses the Overall Equipment Effectiveness (OEE) method to measure the blowing machine effectiveness at the plastic bottle manufacturing plant. This paper investigates losses that gave the biggest impact on machine effectiveness value. Afterwards analytical methods are used in this paper, using Failure Mode and Effect Analysis (FMEA) and Logic Tree Analysis (LTA). Both methods identify as many causes as the failure that can decrease machine effectiveness. OEE value was influenced by low-performance efficiency. Failure that most affect the effectiveness of the machine is shown by factors with the value of Risk Priority Number (RPN) above the critical value.